Leed core conceps guide: An introduction to LEED and green building. - U.S. Green Building Council (Washington, DC : U.S. Green Building Council, 2012)
Presents green building concepts and strategies and introduces the ideas and practices that serve as the foundation for more detailed study of green building.
Green building -- U.S. green building council and its programs -- Sustainable sites -- Water efficiency -- Energy and atmosphere -- Materials and resources -- Indoor environmental quality -- Innovation in design.
Includes bibliographical references.
Keywords: Sustainable buildings -- Design and construction; Leadership in Energy and Environmental Design Green Building Rating System